DEVELOPMENT OF A METHOD FOR DETERMINATION OF METALLIC IRON CONTENT FROM STEEL-MAKING MATERIAL - morcali, mehmet hakan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The growing use of metallic iron in metallurgy and industrial chemical applications requires a fast, easy and cheap method for the determination of metallic iron, not merely in recyclable materials, such as iron pellets, reduced iron mill scale dust, electric arc furnace dust and pig iron, but from hot briquette iron (HBI) as well. This study investigates a new quantitative determination of metallic iron within HBI used for steel-making materials. The effects of reaction time, temperature, and stirring rate were studied. The concentration of iron was determined via Atomic Absorption Spectroscopy (AAS). After the optimization study, high-purity metallic iron powder (Sigma-Aldrich, PubChem Substance ID 24855469) was used to compare efficiencies and identify the optimum conditions; this method was matched with international standard methods (BS ISO 5416:2006, IS 15774:2007). Results were consistent with certified values and metallic iron content could be determined within the 95% confidence level. The purposed method is easy, straightforward, and cheap.